Menanamkan Mental Wirausaha Sejak Dini Untuk Mencetak Generasi Pemimpin Masa Depan - Ahmad Syafii Harahap; Anisa Nur Fitria; Audia Safira Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
Rapid social, economic, and technological changes require youth to develop an entrepreneurial mindset beyond academic skills. This community service project (PKM) at SMK Pupita Bangsa aimed to instill entrepreneurial mentality through an innovative learning module emphasizing leadership, risk-taking, creativity, and project-based learning. The objectives were to provide comprehensive conceptual understanding of entrepreneurial mentality, embed values such as independence, responsibility, risk-taking courage, discipline, and creativity, develop entrepreneurial mindset through reflective and contextual learning, and train basic leadership skills. The method employed an educative, participatory approach: module development tailored to student characteristics, interactive presentations, group discussions, mentoring, project-based assignments, and evaluation via observation, individual and group reflection, and open discussion. Results indicated positive shifts in student mindsets: initial risk-averse perceptions transitioned to recognizing risk as manageable; students showed increased confidence, independence, responsibility, creativity, idea generation, teamwork, and basic leadership. Participants produced simple business ideas and practical marketing approaches aligned with digital trends. The study concludes that innovative, experiential entrepreneurship modules effectively foster entrepreneurial mindset and leadership readiness in vocational students and recommends wider curricular integration.